1999
DOI: 10.1001/archinte.159.18.2129
|View full text |Cite
|
Sign up to set email alerts
|

A Community-Based Study of Chronic Fatigue Syndrome

Abstract: Chronic fatigue syndrome is a common chronic health condition, especially for women, occurring across ethnic groups. Earlier findings suggesting that CFS is a syndrome primarily affecting white, middle-class patients were not supported by our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
557
13
15

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 708 publications
(617 citation statements)
references
References 47 publications
32
557
13
15
Order By: Relevance
“…Il to 21 % (Wessely, 1997;Buchwald et al, 1987) while community studies report a prevalence of 0.2 to 0.6% (Steele et al, 1998;Lawrie & Pelosi, 1995;Jason et al, 1999).…”
Section: Chronic Fatigue Syndrome (Cfs)mentioning
confidence: 99%
“…Il to 21 % (Wessely, 1997;Buchwald et al, 1987) while community studies report a prevalence of 0.2 to 0.6% (Steele et al, 1998;Lawrie & Pelosi, 1995;Jason et al, 1999).…”
Section: Chronic Fatigue Syndrome (Cfs)mentioning
confidence: 99%
“…Conversely conditions involving hypocortisolism may be more strongly related to sex steroid suppression of the HPA axis and promotion of HPG function, a configuration seemingly available only to female subjects. This would suggest that the hypocortisolism seen in diseases, such as CFS [54][55][56], may be a result of the complexity afforded to the interaction between the HPA and HPG in female subjects, and may be an explanation for the reported prevalence of such diseases in women [57][58][59][60][61][62]. Indeed, these authors report that approximately 70% of observed CFS patients are women.…”
Section: Discussionmentioning
confidence: 99%
“…If they did, the team brought them into clinics for evaluation. As a result of the findings from this 4 and other studies, the CDC removed the word 'rare' from its description of the syndrome. In 2015, a report 5 from the US Institute of Medicine (IOM) estimated that 836,000 to 2.5 million Americans have the disorder.…”
Section: Early Daysmentioning
confidence: 98%